Attention Deficit Hyperactivity Disorder in Pediatric Ages: Role of Primary Health Care: Perturbação de Hiperatividade e Défice de Atenção em Idade Pediátrica: Papel dos Cuidados de Saúde Primários - Marques, Maria Inês; Matias, Joana; Machado, Raquel; Duarte, Ana; Fonseca, Maria José; Monteiro, José Paulo (Gazeta Médica, 2018)
Attention deficit hyperactivity disorder (ADHD) is one of the most frequent developmental disorders in pediatric ages. It is characterized by behavioral manifestations that affect the functioning and development of the child/ adolescent, in different contexts. Family doctors are essential in approaching ADHD, by establishing a partnership with the family and due to regu-lar follow-up on child health consultation. In this article, the authors describe the main characteristics of ADHD, including comorbidities, diagnosis and therapeutic intervention, but above all the role of family doctors in screening this disorder and referencing to specialized services but also in the follow-up of these patients.